2019
DOI: 10.1021/acsaem.9b01909
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Relationship between Ti4+ Doping and Li+ Mobility Enhancement in Ti4+ Doped Li3V2(PO4)3

Abstract: The electrochemical properties of Li3V2(PO4)3 (LVP) cathode of lithium ion batteries are often improved by ion doping. Nevertheless, the mechanism of ion doping has not been fully understood. Here, Ti4+ has been chosen as a typical dopant with similar atomic radius to the six-coordinated V3+. A series of Li3Ti x V(2–x)(PO4)3/C samples are successfully synthesized by a sol–gel route. The 7Li MAS NMR spectra of the LT x VP/C demonstrate that the doping of Ti4+ can enhance the mobility of Li ions. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This enhanced rate performance can be attributed to two factors: (1) improvement in electronic conductivity due to the mitigation of inductive effects from Ti 4+ doping and (2) enhancement in Li + diffusion via the formation of vacancies at Li sites. 31…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This enhanced rate performance can be attributed to two factors: (1) improvement in electronic conductivity due to the mitigation of inductive effects from Ti 4+ doping and (2) enhancement in Li + diffusion via the formation of vacancies at Li sites. 31…”
Section: Resultsmentioning
confidence: 99%
“…This result aligns with previous studies, which reported improved rate capacities of Ti 4+substituted LVP due to enhanced Li diffusion through the formation of Li vacancies. 27,31,40,41 Therefore, the higher capacity observed in Ti-LVP than LVP can be attributed to improved rate properties resulting from Ti 4+ substitution and the formation of Li vacancies.…”
Section: Cycle Characteristics In a Full Cell Of Lvp Substituted With...mentioning
confidence: 99%
See 2 more Smart Citations
“…4a. In order to describe the relationship between the potential E and the time T , Fick's second law is used as follows: 49–51 …”
Section: Resultsmentioning
confidence: 99%